Programming in Visual Basic 2010 - Bradley, Julia Case (McGraw-Hill, 2011)
The author team of Julia Bradley and Anita Millspaugh remain the guiding light for countless students around the world in Programming with Visual Basic 2010. How better to master the most popular object-oriented programming language than to use the bestselling textbook? Be at the cutting edge of technology with examples, feedback questions, and a full Hands On Programming Example. Apply the concepts yourself with Case Studies and Exercises. Screen captures, step-by-step exercises, and thorough appendices ensure that Programming Excellence Begins Here.